A STUDY OF ENGLISH COMMUNICATIVE COMPETENCE AT THE TERTIARY LEVEL OF EDUCATION BASED ON EUROPEAN FRAMEWORK OF REFERENCE - Ratini Setyowati; Beta Setiawati; Desi Rohmah Khurniawati (Universitas Duta Bangsa Surakarta, 2022)
CEFR has become a very significant framework for the design of language curricula and the assessment of language learning outcomes. The purpose of the study is to know the CEFR level of the graduate candidate at the Tertiary Level of Education.Â This research used descriptive qualitative method. The researchers took the data from Computer Science Faculty graduate candidates Universitas Duta Bangsa Surakarta in the academic year 2021/2022. There were 359 participants, 346 participants took the test, and 13 participants did not take test. The participant took TOEIC-Like test written by Shinâ€™s book (2015) titled Pre-Intermediate Level Taking the TOEIC: Skills and Strategies, practice test one. The study showed that the highest TOEIC score was 930, and the participant was from the Technical Information study program. Based on TOEIC Test Mapping on the CEFR, the participant was at C1 level or mastery level. There were 12 participants at the B2 level or Vantage Level, and there were 35 participants at the B1 Level. Most participants were at the A2 level or Basic user because 241 participants got a 225-545 TOEIC score (A2) and there were 57 participants at the A1 level.